Sedimentary Environment Reconstruction and Organic Matter Enrichment Mechanisms in Various Lithofacies of the Lacustrine Shale: A Case Study of the Da’anzhai Member, Central Sichuan Basin, China - Yuting Peng; Yingxiao Fu; Senran Chen; Enze Wang (Applied Sciences)
Jurassic lacustrine shale in the Sichuan Basin is a focal exploration area in China, while the pronounced heterogeneity presents challenges, necessitating detailed research as a prerequisite. This study aims at the Jurassic Ziliujing Formation Da’anzhai shale in the central Sichuan Basin, systematically characterizing its geological features. Employing geochemical methods, we reconstructed the paleo-sedimentary environments and explored the mechanisms behind the organic matter enrichment. The findings reveal that the Da’anzhai shale exhibits three lithofacies: organic-rich argillaceous shale (ORA), organic-poor argillaceous shale (OPA), and organic-rich mixed shale (ORM). The sedimentary period was marked by a warm and humid climate, predominantly depositing in anoxic environments with freshwater to brackish conditions. The watershed areas that are provenance sources for the shale clastics are experiencing strong weathering. Significant differences in the sedimentary environments of various lithofacies’ shale were observed. Redox conditions and paleoclimate were identified as the primary factors controlling organic matter enrichment in the Da’anzhai shale of the study area. Salinity also played a role in organic matter enrichment, while terrigenous debris influx and paleo-productivity did not exert a significant controlling effect on organic matter enrichment. Utilizing the reconstructed ancient sedimentary environments, we developed sedimentary models for different lithofacies’ shale, contributing to a deeper understanding of lithofacies’ diversity and the mechanisms governing organic matter enrichment in lacustrine environments. This study provides new information for further understanding the response mechanism of lacustrine shales to the Toarcian Oceanic Anoxic Event in the Early Jurassic from the perspective of elemental geochemistry.